A diminutive species of emu (Casuariidae: Dromaiinae) from the late Miocene of the Northern Territory, Australia. Issue 4 (4th July 2019) - Yates, Adam M.; Worthy, Trevor H.
ABSTRACT: A new, diminutive species of dromaiine casuariid, Dromaius arleyekweke, is described from dispersed skeletal elements from the late Miocene Waite Formation of the Northern Territory, Australia. Remains of D. arleyekweke, sp. nov., have been found from the Ongeva Local Fauna in the Alcoota Scientific Reserve, but most remains come from the stratigraphically lower Alcoota Local Fauna where they form part of a densely fossiliferous series of mingled bone beds. Previously, remains of the new species had been referred to the basal dromaiine genus, Emuarius, but phylogenetic appraisal of new specimens indicates that the species shared a more recent common ancestor with the extant Dromaius novaehollandiae than it did with the type species of Emuarius, E. gidju . Consequently, the new species is placed in the genus Dromaius as its oldest known member. Derived characters of D. arleyekweke that are shared with D. novaehollandiae to the exclusion of E. gidju include a distally flattened external condyle of the distal end of the tibiotarsus and a more elongate tarsometatarsus, with marked transverse compression of the midshaft and a weakly impressed median sulcus on trochlea metatarsi II. Casuariid evolution shows a trend of increasingly cursorial hind limb proportions on the emu lineage, but D. arleyekweke has a tarsometatarsus that is more elongate than that of D. novaehollandiae . This implies nonlinear evolution of cursoriality in dromaiines and that D. arleyekweke evolved extreme cursorial proportions independently of D. novaehollandiae, or that a high degree of cursoriality evolved early in Dromaius and was reversed in the Pliocene D. ocypus .